2015
DOI: 10.1111/phor.12091
|View full text |Cite
|
Sign up to set email alerts
|

Automated Fish Detection in Underwater Images Using Shape‐Based Level Sets

Abstract: Underwater stereo-video systems are widely used for the measurement of fish. However, the effectiveness of stereo-video measurement has been limited because most operational systems still rely on a human operator. In this paper an automated approach for fish detection, using a shape-based level-sets framework, is presented. Knowledge of the shape of fish is modelled by principal component analysis (PCA). The Haar classifier is used for precise localisation of the fish head and snout in the image, which is vita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(28 citation statements)
references
References 28 publications
0
28
0
Order By: Relevance
“…Erik Rodner et al [15] This method depends upon the convolutional neural networks that is done on the objects in order to detect and also for the classification of species. Here the removal of background is proposed which are filtered using the binary SVM classifier for the classification of fishes.…”
Section: Related Workmentioning
confidence: 99%
“…Erik Rodner et al [15] This method depends upon the convolutional neural networks that is done on the objects in order to detect and also for the classification of species. Here the removal of background is proposed which are filtered using the binary SVM classifier for the classification of fishes.…”
Section: Related Workmentioning
confidence: 99%
“…In addition, adaptive control provides an ability to re-adjust the controller parameters online to achieve the required performance when the process parameters are unknown and vary over time [35]. In contrast to the motion control of fully actuated AUVs, the main concern in the design of controllers for underactuated AUVs is that the number of their independent actuators is fewer than degrees of freedom [36]. This feature increases the degree of complexity in the design of nonlinear tracking controllers for such systems.…”
Section: Introductionmentioning
confidence: 99%
“…Recent research in automated analysis of underwater videos has shown promising results for detection, counting, and species identification of fish of interest in partially or fully uncontrolled environments (Charalampidis et al, 2012;Boom et al, 2014;Ravanbakhsh et al, 2015;Salman et al, 2016;Shafait et al, 2016;Shortis et al, 2016). However, in general, these systems are not capable of fully automated operation or do not attempt length measurement, as they have been developed for single camera operations with the primary aim of identifying and counting species of interest.…”
Section: Introductionmentioning
confidence: 99%